Brain MRI shows white matter sparing in Kennedy's disease and slow‐progressing lower motor neuron disease. Issue 10 (28th March 2019) - Spinelli, Edoardo G.; Agosta, Federica; Ferraro, Pilar M.; Querin, Giorgia; Riva, Nilo; Bertolin, Cinzia; Martinelli, Ilaria; Lunetta, Christian; Fontana, Andrea; Sorarù, Gianni; Filippi, Massimo
Abstract: The extent of central nervous system involvement in Kennedy's disease (KD) relative to other motor neuron disease (MND) phenotypes still needs to be clarified. In this study, we investigated cortical and white matter (WM) MRI alterations in 25 patients with KD, compared with 24 healthy subjects, 25 patients with sporadic amyotrophic lateral sclerosis (ALS), and 35 cases with lower motor neuron‐predominant disease (LMND). LMND patients were clinically differentiated into 24 fast and 11 slow progressors. Whole‐brain cortical thickness, WM tract‐based spatial statistics and corticospinal tract (CST) tractography analyses were performed. No significant difference in terms of cortical thickness was found between groups. ALS patients showed widespread decreased fractional anisotropy and increased mean (MD) and radial diffusivity (radD) in the CST, corpus callosum and fronto‐temporal extra‐motor tracts, compared with healthy controls and other patient groups. CST tractography showed significant alterations of DT MRI metrics in ALS and LMND‐fast patients whereas KD and LMND‐slow patients were comparable with healthy controls. Our study demonstrated the absence of WM abnormalities in patients with KD and LMND‐slow, in contrast with diffuse WM damage in ALS and focal CST degeneration in LMND‐fast, supporting the use of DT MRI measures as powerful tools to differentiate fast‐ and slow‐progressing MND syndromes, including KD.